Recurrent herpes simplex infections: laser therapy as a potential tool for long-term successful treatment - Dennis Carvalho Ferreira; Helena Lucia Barroso Reis; Fernanda Sampaio Cavalcante; Kátia Regina Netto dos Santos; Mauro Romero Leal Passos (Revista da Sociedade Brasileira de Medicina Tropical, 2011)
Herpes simplex virus types 1 and 2 are the main infectious agents associated with oral and genital ulcerations. These infections are now widely recognized as sexually transmitted diseases. Among treatment options, low-level laser therapy (LLLT) has shown promising clinical results as a longer-lasting suppression therapy. Two clinical cases are described with recurrent labial herpes for which LLLT was used. Following treatment, both patients remained symptom free during the 17-month clinical follow-up period.